2021
DOI: 10.1371/journal.pone.0254261
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of aspiration pneumonia patients in acute care hospitals: A multicenter, retrospective survey in Northern Japan

Abstract: Background Pneumonia is a common cause of illness and death of the elderly in Japan. Its prevalence is escalating globally with the aging of population. To describe the latest trends in pneumonia hospitalizations, especially aspiration pneumonia (AP) cases, we assessed the clinical records of pneumonia patients admitted to core acute care hospitals in Miyagi prefecture, Japan. Methods A retrospective multi-institutional joint research was conducted for hospitalized pneumonia patients aged ≥20 years from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Currently, microorganism such as Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae, and Enterobacteriaceae are the most common organisms. In a recent retrospective multi-institutional joint research from Japan were 1,800 patients with pneumonia were included, the ratio of aspiration pneumonia to total pneumonia cases increased with age, and 38% of the patients had aspiration pneumonia [11]. There were significant differences between the microbial etiology between patients with aspiration pneumonia and patients without aspiration pneumonia, with a higher frequency of S. aureus, Klebsiella spp., and Escherichia coli, and a lower frequency of S. pneumoniae, and H. influenzae in the aspiration group.…”
Section: Clinical Features Of Aspiration Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, microorganism such as Streptococcus pneumoniae, Staphylococcus aureus, Haemophilus influenzae, and Enterobacteriaceae are the most common organisms. In a recent retrospective multi-institutional joint research from Japan were 1,800 patients with pneumonia were included, the ratio of aspiration pneumonia to total pneumonia cases increased with age, and 38% of the patients had aspiration pneumonia [11]. There were significant differences between the microbial etiology between patients with aspiration pneumonia and patients without aspiration pneumonia, with a higher frequency of S. aureus, Klebsiella spp., and Escherichia coli, and a lower frequency of S. pneumoniae, and H. influenzae in the aspiration group.…”
Section: Clinical Features Of Aspiration Pneumoniamentioning
confidence: 99%
“…Microaspiration is recognized as the main pathogenic mechanism in pneumonia where particulate material and microorganisms are able to enter upper airways and then reach the lower airways and respiratory tract; while macroaspiration which refers to the aspiration of a large-volume of oropharyngeal or upper gas-trointestinal content passing through the trachea and larynx into the lungs describes the term "aspiration pneumonia" [1]. Approximately, between 10% to 30% of hospitalized patients with a diagnosis of community-acquired pneumonia have an illness related to aspiration [2][3][4]. However, numbers related to aspiration in patients with hospital-acquired pneumonia are scarce.…”
mentioning
confidence: 99%
“…The incidence in cases of Community Acquired Pneumonia (CAP) and HAP was 60.1%, 86.7% and Aspiration Pneumonia (AP) accounted for 66.8% of the total pneumonia inpatients. This number is closely related to patients aged 65 years as many as 22 ,1% in 2018 (Suzuki et al, 2021). Nonventilator Hospital Acquired Pneumonia (NV-HAP) risk is noticed higher when the patients stay increases.…”
Section: Introductionmentioning
confidence: 98%
“…Recent researches on the inflammatory biomarker procalcitonin (PCT) and new blood biomarkers, for example, NLR (neutrophilic granulocyte/lymphocyte ratio) and PLR (platelet cell count/lymphocytes) are also being used. A recent multicenter retrospective study in northern Japan found that, compared with non-AP, AP patients have lower BMI (19.4 ± 4.0 vs. 21.4 ± 4.6), C-reactive protein (9.4 ± 8.5 vs. 11.5 ± 9.8 mg/dL), and serum albumin (3.1 ± 0.6 vs. 3.2 ± 0.6) g/dL); higher rates of cerebrovascular disease, dementia and neuromuscular disease complications; and higher mortality rates ( Suzuki et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%